2014
DOI: 10.3329/bjms.v13i2.18301
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Nigerian Honey on Sperm indices and Testis in Sucrose-Fed Rats

Abstract: Objective: This study aimed at investigating the effect of high sucrose diet on male reproductive function and if Nigerian honey could exert a protective role. Methods: Twenty-four (24) rats were randomly divided into four equal groups of six animals and given water (control); honey (H); high sucrose solution (30%w/v) (HSS); and both high sucrose solution (30%w/v) and honey (HSS+H). Each rat on honey received a daily dose of 10ml honey/kg/5ml of distilled water. Food intake, body weight, organ weight, fasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…It regained the normal appearance of the epididymal structure with a highly increase in the number of sperm inside its tubules. While Mohamed et al, (2012) revealed that no significant change in the epididymal weight was induced by honey consumption, Abdul-Ghani et al (2008) and Oyelowo et al (2014) reported that honey supplementation to rats increased epididymal weight significantly. To the best of our knowledge, no previous study has been undertaken to investigate the beneficial effects of honey on the epididymal histology.…”
Section: Discussionmentioning
confidence: 98%
“…It regained the normal appearance of the epididymal structure with a highly increase in the number of sperm inside its tubules. While Mohamed et al, (2012) revealed that no significant change in the epididymal weight was induced by honey consumption, Abdul-Ghani et al (2008) and Oyelowo et al (2014) reported that honey supplementation to rats increased epididymal weight significantly. To the best of our knowledge, no previous study has been undertaken to investigate the beneficial effects of honey on the epididymal histology.…”
Section: Discussionmentioning
confidence: 98%
“…These findings were supported by numerous studies in which administration of different types of honey to normal and diabetic rats exhibited no negative impact on the testicular weights (Michael et al, 2015;Mohamed et al, 2012;Syazana et al, 2011). Moreover, Oyelowo et al (2014) reported that honey supplementation to rats increased testicular weight significantly. The improvement of testicular weight via Trihoney administration could be through the enhancement of spermiogenesis and spermatogenesis by maintaining testicular integrity and optimizing neuroendocrine gonadal axis with an elevation of testosterone hormone and a subsequent improvement in spermatogenesis as shown previously with other types of honey (Abdul-Ghani et al, 2008;Kenani et al, 2015;Michael et al, 2015;Mohamed et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of honey on male reproductive hormones has been investigated in various studies but this is the first study attempts to determine the effect of honey on male reproductive hormonal disturbances induced by hypercholesterolaemia. Oyelowo et al (2014) 9 reported that consumption of honey increased testosterone and reduced FSH and LH in rats fed with normal diet and rats received high sucrose solution. The beneficial effect of honey in increasing low serum testosterone, and reducing elevated serum FSH and LH was detected in noise-exposed rats.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,7 On the other hand, the use of honey in previous studies resulted in an improvement of the male reproductive hormonal disturbances through increasing testosterone and reducing FSH and LH in rats fed with high sucrose diet and rats exposed to noise stress. 8,9 Trihoney is a product developed by the Department of Nutrition Sciences of Kulliyyah of Allied Health Sciences of International Islamic University Malaysia. It is a mixture of Trigona, Mellifera and Tualang honey at a ratio optimized by Response Surface Methodology of Design Expert Version 6.0 software.…”
Section: Introductionmentioning
confidence: 99%